KARAKTERISTIK ANATOMI, FISIK MEKANIK, PENGERINGAN DAN KETERAWETAN KAYU KEMIRI (Aleurites moluccana Willd.) - Muhammad Asdar; Mody Lempang (PERENNIAL, 2006)
The aim of this research was to determine the anatomy, physical and mechanical properties, drying characteristics and treatability of kemiri wood. The observed paramaters were macroscophic and microscophic characteritics, moisture content, specific grafity, shrinkage, strength properties, drying quality, and the retention and penetration of wood preservative. Tests were run according to IAWA List, SNI and JIS. The heartwood colour is white to yellowish white and it is not clearly demarcated to the sapwood. Wood texture is rather coarse, stright grain, rather rough and rather glossy surface. The vessels are oval, diffuse porous, simple perforation plates. Parenchyma type is incomplete borders to the vessels and short tangential lines. Rays heterocellular are uniseriate and biseriate. Its fiber length is medium long size. Kemiri wood is classifed to strength class IV-III. Retention and penetration of wood preservative after 5 days in cold water treatment was met to SNI standard. The air drying test indicated the need of 8 days to achieve of the moisture content 12,29%. Wood defects due to the air drying test can be occured in the forms of check, bowing, discolouration and blue stain. Keywords: Wood anatomy, physical, mechanical, drying, treatability, Aleurites mollucana References